Oxidative Fluorination of Cu/ZnO Methanol Catalysts. Issue 37 (4th July 2019) - Dybbert, Valentin; Fehr, Samuel Matthias; Klein, Florian; Schaadt, Achim; Hoffmann, Anke; Frei, Elias; Erdem, Emre; Ludwig, Thilo; Hillebrecht, Harald; Krossing, Ingo
Abstract: The influence of a mild difluorine treatment on Cu/ZnO precatalysts for methanol synthesis was investigated. It led to the incorporation of 1.2…1.3±0.1 wt % fluoride into the material. Fluorination considerably increased the amount of ZnOx related defect sites on the catalysts and significantly increased the space‐time yields. Although the apparent activation energy E A, app for methanol formation from CO2 and H2 was almost unchanged, the E A, app for the reverse water‐gas shift (rWGS) reaction increased considerably. Overall, fluorination led to a significant gain in methanol selectivity and productivity. Apparently, also the quantity of active sites increased. Abstract : Fluorinated Catalysts? By exposure of Cu/ZnO precatalysts to gaseous F2, fluoride was incorporated into the material. After activation, the catalytic properties of the F‐Cat systems change significantly, increasing the performance for methanol synthesis and disfavoring the reverse water‐gas shift reaction when starting from CO2 and H2 .